Financial Ratios' Effect on Stock Prices in Banking Subsector Companies - Arifin, Childan Berlian; Zulbetti, Rita; Perwito, Perwito (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2024)
This research analyzed the impact of financial ratios on stock prices in banking companies listed on the IDX from 2020 to 2023. Using a sample of 19 companies selected through purposive sampling from 47 issuers, the study examined Profitability (ROA, ROE), Solvency (DER), and Market Value (PBV) ratios. The findings show that ROE and PBV have a positive and significant impact on Stock Prices, suggesting that investors value companies with strong equity returns and market valuation. In contrast, ROA and DER do not significantly influence stock prices, indicating that asset utilization and debt levels may not be major considerations for investors in this sector. These results provide valuable insights for investors and regulators, underscoring the importance of financial ratios in making informed investment decisions and understanding stock price movements in the banking industry. Keywords: Profitability Ratios; Solvency Ratios; Market Value Ratios; Stock Prices; Banking